Adaptation of Spiritual Intelligence Scale for Turkish: a validity and reliability study - Tekke, Mustafa ca. 20./21. Jh. (Spiritual care, 2025)
Background: This manuscript adapts the concept of spiritual intelligence, examining its growing significance and its potential benefits to Turkish literature. Objective: It delves into the concept of spiritual intelligence, outlining its components like critical existential thinking, personal meaning production, transcendent awareness, and conscious state expansion. Method: A total of 382 participants were recruited accordingly. Confirmatory factor analysis (CFA) supported a single-factor model for the Turkish version of Spiritual Intelligence Scale (SIS), indicating good fit with the data. Reliability was assessed using Cronbach's alpha (.80) and test-retest reliability (.86), demonstrating the scale's internal consistency and stability. Item-total correlations ranged from .13 to .62, with all items significantly correlating with the total score. Conclusion: The manuscript adapts the SIS into the Turkish language. These findings suggest the SIS is a valid and reliable tool for measuring spiritual intelligence in Turkish-speaking populations.